Sustainable Urban Drainage System (SUDS) – Malaysian Experiences. - Ab Ghani, A; Zakaria, Nor Azazi; C, K Chang; Ainan, A (2008)
Sustainable Urban Drainage Systems (SUDS) have been used widely in USA, Europe, Japan and Australia to name a few developed countries.